DEVELOPMENT OF MATHEMATICS LEARNING PACKAGE WITH GEOGEBRA-ASSISTED SCIENTIFIC APPROACH FOR THE EIGHT GRADERS - Nurwijaya, Sugian (Sains Global Institut, 2019)
This is a research and developmentstudy with limited trials which aims to develop the Mathematics Learning Package by using a geogebra-assisted scientific approach in the eight grade of MTs Al-Junaidiyah Biru, Bone Regency. Such learning package includes student books, student activity sheets, learning implementation plans and learning outcomes test. The subjects of this study were twenty two students of class VIIIC MTs Al-Junaidiyah Biru Bone Regency. The development procedure used in this study is the Thiagarajan model or 4D model (Define, Design, Develop, and Disseminate) which includes four phases, namely the limitation, the design, the development, and the small scale distribution phase. Learning packagewith geogebra-assisted scientific approach that had been developed have been validated by experts and have been revised so that results are feasible to use. The results of limited trials show that the learning package produced has been practical and effective. (4) skor rata-rata yang diperoleh siswa pada tes hasil belajar adalah 78,40 dari skor ideal 100 dengan standar deviasi 11,89. Dimana 19 dari 22 siswa atau 86,36% memenuhi ketuntasan individu yang menunjukkan bahwa ketuntasan klasikal tercapai.The results of data analysis are as follows: (1) teacher activities can guide groups to work and learneffectively; (2) students generally give the positive responses to the developed learning package; (3) mathematics learning package with geogebra-assisted scientific approach make students more active in the learning process; (4) the average score obtained by students on the learning outcomes test is 78.40 from the ideal score of 100 with a standard deviation of 11.89. Then, 19 of 22 students or 86.36% fulfilled individual completeness which shows that classical completeness was achieved